2002
DOI: 10.1136/heart.87.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal myocardial contraction improves early during titration with metoprolol CR/XL in patients with heart failure

Abstract: Objective: To investigate diastolic and systolic left ventricular recovery during titration with metoprolol CR/XL (controlled release/extended release). Design: Placebo run in, followed by an open study. Setting: University hospital. Patients: 14 patients with chronic heart failure. Interventions: Metoprolol CR/XL titrated from 12.5 mg once daily to 200 mg once daily. Main outcome measures: M mode recordings of atrioventricular (AV) plane displacement, Doppler measurement of transmitral flow and pulmonary veno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 25 publications
(22 reference statements)
0
14
0
Order By: Relevance
“…Borges et al 24 found acute treatment with captopril had no significant effect on either Sm or Em in subjects with hypertension with or without LVH. In heart failure subjects Andersson et al 28 found that treatment with metoprolol CR/XL led to an increase in atrioventricular plane displacement after 6 weeks. In patients with heart failure and normal ejection fraction diuretics combined with irbesartan or ramipril led to a small but significant improvement in longitudinal velocities 29.…”
Section: Discussionmentioning
confidence: 99%
“…Borges et al 24 found acute treatment with captopril had no significant effect on either Sm or Em in subjects with hypertension with or without LVH. In heart failure subjects Andersson et al 28 found that treatment with metoprolol CR/XL led to an increase in atrioventricular plane displacement after 6 weeks. In patients with heart failure and normal ejection fraction diuretics combined with irbesartan or ramipril led to a small but significant improvement in longitudinal velocities 29.…”
Section: Discussionmentioning
confidence: 99%
“…More interestingly, the recovery of long axis function actually precedes that of short axis [16]. We feel, therefore, that our findings are clinically relevant.…”
Section: Discussionmentioning
confidence: 47%
“…We have previously shown that basal LV function is important for long-term recovery, and that metoprolol treatment exerts effects in these segments early after institution of therapy [8]. The cellular mechanism behind the ability of metoprolol treatment to recruit contractility in the basal segments is not known.…”
Section: Function and Recovery Of Basal Segments Of The Left Ventriclementioning
confidence: 98%
“…Each segment contained 16 chords except segments 6, 7, 10, 12, 13 and 16 that contained 17 chords. LV regional function was evaluated in three sections of the left ventricle: the basal segments (segments 2, 4, 7, 10, 13, 16); mid segments (segments 1, 3, 6, 9, 12, 15); and apical segments (segments 5,8,11,14) as shown in Fig. 1.…”
Section: Echocardiographic Measurementsmentioning
confidence: 99%
See 1 more Smart Citation